Sperm Nuclear Vacuoles in relation to Acrosome Reactions and Sperm Motility. (3rd July 2014) - Komiya, Akira; Kawauchi, Yoko; Kato, Tomonori; Watanabe, Akihiko; Tanii, Ichiro; Fuse, Hideki
Abstract : We investigated sperm nuclear vacuolation in relation to acrosome reactions and the maintenance of sperm motility. Thirty male patients who visited our Male Infertility Clinic were enrolled. These patients underwent conventional semen analyses, Acrobeads tests, and high-magnification observation of the sperm head to evaluate the degree of nuclear vacuolation on the Acrobeads test scoring after 24 hours of incubation. The presence of acrosome reactions was evaluated using the Acrobeads test. The spermatozoa were classified into three groups: (I) those bound to MH61-beads, (II) motile spermatozoa that did not bind to MH61-beads, and (III) immotile spermatozoa that did not bind to MH61-beads. The percentage of spermatozoa with large nuclear vacuoles (%LNV) was compared between the three groups. The degree of sperm nuclear vacuolation was evaluated in 17, 992 ejaculated spermatozoa. The mean %LNVs were 2.4% in group I, 5.8% in group II, and 9.8% in group III. These values were significantly different from each other (P < 0.001, paired t -test). There were no correlations between the %LNV values and the Acrobeads scores. In conclusion, the degree of sperm nuclear vacuolation was significantly lower in the acrosome-reacted spermatozoa and spermatozoa with maintained motility, and higher in the immotile spermatozoa that did not bind to MH61-beads.